Bisignate resonance Raman optical activity: a pseudo breakdown of the single electronic state model of RROA?. (14th August 2014) - Zajac, Grzegorz; Kaczor, Agnieszka; Chruszcz‐Lipska, Katarzyna; Dobrowolski, Jan Cz.; Baranska, Malgorzata
<x xml:space="preserve">Abstract</x> Raman optical activity (ROA) spectra were calculated for a set of conformers of astaxanthin, which is a non‐rigid molecule exhibiting strong resonance enhancement in the visible range. Single electronic state theory of the Resonance ROA (RROA) predicts the spectrum to be monosigned. For astaxanthin, it appeared that some of the conformers exhibit different sign of the bands than the other conformers. As a result, the conformer population averaged spectrum of astaxanthin can exhibit both signs of the bands, or be monosigned depending on which conformers are dominating, that reflects a departure from the single electronic state approximation. Moreover, use of different basis sets and/or density functional theory (DFT) functionals results in different conformer populations, thus yielding again either monosigned ROA spectrum or with bands of both signs. Consequences of these two findings for the astaxanthin RROA spectrum are discussed. Copyright © 2014 John Wiley & Sons, Ltd.